Dampak Ekonomi dan Strategi Pengembangan Wisata Danau Sentani di Kabupaten Jayapura - Ditha Mangiri; Hermanto Siregar; Ernan Rustiadi (P4W LPPM IPB, 2020)
Economic Impacts and Development Strategies for Lake Sentani Tourism in Jayapura Regency Lake Sentani tourism is a type of natural tourism. Management of the natural tourism is in the form of collaboration between the local government and local communities by relying on the beauty and panorama of the nature. Aims of this study are (1) to estimate the economic value of Lake Sentani tourism which is expected to have an impact to the local economy and benefit the surrounding communities, and (2) to formulate effective strategies for managing the natural tourism. Data collection was conducted through field survey and interview. Data used were on tourist expenditure, labor, business income, number of tourists, and perceptions and preferences of stakeholders towards the development of Lake Sentani tourism. The sampling method used was the purposive sampling technique with a total sample of 133 persons. The method of analysis used were Individual Travel Cost Method (ITCM), multiplier effect, and Analytic Hierarchy Process (AHP). Analysis results show that Lake Sentani tourism had a low economic impact on the local economy development and communities around the area with a value of Keynesian income multiplier of 0.93. In order to develop Lake Sentani tourism, the proposed strategy is ecologically based, supported by the role of local government stakeholder as regulator who are responsible for advancing the welfare of business people involved in all activities related to Lake Sentani tourism.